2020
DOI: 10.4014/jmb.2006.06050
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Plant Growth-Promoting Effects of Fungal Endophytes Isolated from Salt-Tolerant Plants

Abstract: Unique microecosystems within the internal tissues of plants support diverse, symbiotic microbial communities that greatly influence plant adaptation and evolution [1, 2]. These microbial associations significantly influence the ability of plants to adapt and evolve in their environment. All plants in natural ecosystems appear to develop symbiotic associations with fungi [3, 4]. These symbioses provide a buffer against biotic and abiotic stresses and are important for the survival of plant hosts and their fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…Endophyte and its host plants formed a harmonious symbiotic relationship during the long-term co-evolution process. Especially, increasing evidences showed that endophyte can directly and indirectly promote the growth and secondary metabolites of its host plants through various ways [ 12 14 ]. For example, endophyte can induced the development of its host plants by directly producing plant growth hormone themselves [ 12 ], or indirectly by promoting its host plants capacity of nutrients absorption and stress resistance [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Endophyte and its host plants formed a harmonious symbiotic relationship during the long-term co-evolution process. Especially, increasing evidences showed that endophyte can directly and indirectly promote the growth and secondary metabolites of its host plants through various ways [ 12 14 ]. For example, endophyte can induced the development of its host plants by directly producing plant growth hormone themselves [ 12 ], or indirectly by promoting its host plants capacity of nutrients absorption and stress resistance [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The genus Cladosporium is a well-known group of fungi that includes some indoor and outdoor molds. Many species of the genus Cladosporium are endophytes that live inside plants, and were found to promote plant growth rather than being pathogenic ( Khalmuratova et al, 2020 ; Sun et al, 2020 ; Faddetta et al, 2021 ; Mao et al, 2021 ; Schmidt et al, 2021 ). However, some species of Cladosporium , including C. fulvum and C. herbarum , are phytopathogenic ( Kaur and Manhas, 2014 ; Elgorban et al, 2017 ; Wang et al, 2018 ), strongly affecting plant growth and health.…”
Section: Discussionmentioning
confidence: 99%
“…Fungal VOCs that have the ability to promote plant growth can avoid potential pathogenicity problems associated with whole organisms as direct contact is not required ( Hamayun et al, 2010 ; Ghirardo et al, 2011 ; Paul and Park, 2013 ; Naznin et al, 2014 ; Li et al, 2018 ; Khalmuratova et al, 2020 ). It could be safer to only apply VOCs as bio-fungicides and growth stimulants to enhance the growth of plants.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to saprobic fungi in halophytes, few studies have been carried out on the diversity of endophytes and pathogens and their interaction in the salt marsh ecosystems. Surveys on endophytic fungi from halophytes using cultivation-dependent methods coupled with molecular approaches, showed that endophytes were dominated by Ascomycota and a few belonged to Basidiomycota and Zygomycota [168][169][170][171][172][173][174][175]. Pathogenic fungi from salt marsh ecosystems are poorly documented but play a significant role in the dynamics of the ecosystem [176][177][178].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%